Laboratory Adequacy and Students’ Attitude: the Determinant of Educational Outcome in Chemistry Practical in Secondary Schools in Ibadan Less City, Nigeria - Olasunkanmi OGUNDIJI (MASI Mandiri Edukasi, 2025)
Chemistry practical helps pupils to understand chemical concepts and create their own learning. Studies have revealed inadequate practical works in chemistry, and identified factors that may be responsible for this fallout with a view to improving the situation but the problem still persists. This study therefore examined if laboratory adequacy and students’ attitude will predict students’ learning outcome in chemistry practical. The population of the study comprised one 150 students and 10 teachers from 5 public senior secondary schools in Ibadan less city, Nigeria. The instruments used are: Chemistry Laboratory Adequacy Inventory (r=0.79), Chemistry Practical Achievement Test (CPAT) (r = 0.81), Students’ Attitudinal Scale (r=0.76). Descriptive and inferential statistics were used. The results revealed: students’ positive attitude in chemistry practical, students’ low achievement, inadequate laboratory facilities. Furthermore, it was revealed that laboratory facilities (β=.022P>.05); students’ attitude in chemistry practical (β=-.102,P >.05); are weak predictors of students’ achievement in chemistry practical. The study therefore recommends that chemistry teachers should improve on teaching chemistry practical, the Government at various levels should endeavor to build science laboratory, employ more chemistry teachers and supply schools with laboratory facilities